Spaces of Danger : Culture and Power in the Everyday - Merrill, Heather (Book collections on Project MUSE., 2015)
"On July 22, 2011 a 32 year old far right activist clothed as a police officer opened fire on a Labor Party youth camp on Utoya Island in Norway, slaughtering 69 people and maiming many more. The vast majority of the victims were between 14 and 19 years of age. He also placed bombs in a government building in Oslo, killing 8 and wounding others. In a 1,500 page manifesto in English posted on the internet hours before the massacres in which he referred to himself as a "Marxist hunter," he declared "preemptive war," targeting "Cultural Marxists" who propagate a "multiculturalist," ideology to which he attributed the decay of Western European and American "civilization and culture" and the promotion of a pro-Islamic "Eurabia." What is compelling about this story is less what the content of the killer's easily downloadable manuscript reveals about far right thinking, than how the significance of the event was concealed and silenced as it was interpreted for the public by journalists and political figures. By characterizing Breivik as an evil 'aberration' and abstracting his acts from the social and political context in which they took place, persuasive political arbiters and media reproduced what Allan Pred referred to as "situated ignorance," keeping people from attaining a more accurate knowledge and understanding of the events"--